INVESTMENT OF SPRITUAL VALUES IN AQIDAH AKHLAK LESSON IN MAS AL-MAKSUM STABAT STUDENTS - Ali Imran Sinaga; Zaini Dahlan; Khairunnisa Abdillah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
Cultivating spiritual values in the subject of aqidah akhlak (Asmaul Husna) in Madrasah Aliyah Swasta Al Maksum Stabat students. This study aims to etermine (1) What are the spiritual values contained in Aqidah Akhlak lessons at Madrasah Aliyah Swasta Al Maksum Stabat. (2) How is the process of internalizing spiritual values in learning Aqidah Akhlak at Madrasah Aliyah Swasta Al Maksum Stabat. (3) What is the teacher's perception of supporting and inhibiting factors in instilling spiritual values through learning Aqidah Akhlak at Madrasah Aliyah Swasta Al Maksum Stabat. The research material was the religion teacher in the field of aqidah akhlak study who was the sample of class X students at Madrasah Aliyah Swasta Al Maksum Stabat.This type of research is qualitative, with descriptive analysis. Data collection tools using interviews, observation, documentation. Analyzing the researcher using two stages, namely data processing and data analysis, in terms of analyzing the data the researcher also uses two methods, namely pre-field analysis and field analysis of the two methods, conclusions can be drawn from the results of the research conducted.The results showed that the spiritual values in the subject of aqidah morals in the material of Asmaul Husna are the value of faith (Tauhid), the value of piety (worship), and the value of morals. The process of inculcating spiritual values carried out by teachers of aqidah akhlak subject in teaching to students is carried out by means of habituation. Factors that support the implementation of learning aqidah akhlak start from what is in the teacher itself.The most supportive factor in this activity is the teacher's strategy and approach to students, then other supporting factors are also inseparable from a good play environment and the most important support from parents. While the inhibiting factors are students who do not obey the rules that have been made, then the implementation time is not right, and the most important thing is the support of parents to take control of their children at home.